Lipid nanocarriers for hyperproliferative skin diseases - Souto, Eliana B. (2021)
Hyperproliferative skin diseases (HSD) are a group of diseases that include cancers, pre-cancerous lesions and diseases of unknown etiology that present different skin manifestations in terms of the degree and distribution of the injuries. Anti-proliferative agents used to treat these diseases are so diverse, including 5-aminolevulinic acid, 5-fluorouracil, imiquimod, methotrexate, paclitaxel, podophyllotoxin, realgar, and corticosteroids in general. These drugs usually have low aqueous solubility, which consequently decreases skin permeation. Thus, their incorporation in lipid nanocarriers has been proposed with the main objective to increase the effectiveness of topical treatment and reduce side effects. This manuscript aims to describe the advantages of using lipid nanoparticles and liposomes that can be used to load diversity of chemically different drugs for the treatment of HSD.